The TFIIIC90 Subunit of TFIIIC Interacts with Multiple Components of the RNA Polymerase III Machinery and Contains a Histone-Specific Acetyltransferase Activity - Hsieh, Yng-Ju (American Society for Microbiology, 1999)
Human transcription factor IIIC (hTFIIIC) is a multisubunit complex that directly recognizes promoter elements and recruits TFIIIB and RNA polymerase III. Here we describe the cDNA cloning and characterization of the 90-kDa subunit (hTFIIIC90) that is present within a DNA-binding subcomplex (TFIIIC2) of TFIIIC. hTFIIIC90 has no specific homology to any of the known yeast TFIIIC subunits. Immunodepletion and immunoprecipitation studies indicate that hTFIIIC90 is a bona fide subunit of TFIIIC2 and absolutely required for RNA polymerase III transcription. hTFIIIC90 shows interactions with the hTFIIIC220, hTFIIIC110, and hTFIIIC63 subunits of TFIIIC, the hTFIIIB90 subunit of TFIIIB, and the human RPC39 (hRPC39) and hRPC62 subunits of an initiation-specific subcomplex of RNA polymerase III. These interactions may facilitate both TFIIIB and RNA polymerase III recruitment to the preinitiation complex by TFIIIC. We show that hTFIIIC90 has an intrinsic histone acetyltransferase activity with a substrate specificity for histone H3.